(untitled) (Journal of Patan Academy of Health Sciences, 2022)
A 38-year-old man, with history of COVID 19 pneumonia 23 days back, non-smoker and known case of hypertension presented to the emergency department with complain of sudden onset multiple episodes of blood mixed sputum associated with shortness of breath and sharp type of left sided chest pain for last five hours. The patient was dyspneic, tachypneic and hypoxemic at the time of examination with SPO2 of 84 to 86% without oxygen which improved to 95-96% after 15 liter/min of oxygen via high flow nasal cannula. There were no breath sounds in left hemi thorax and decreased breath sound on right side with basal crepitation. Chest radiograph revealed left sided pneumothorax, needle decompression done immediately followed by chest tube insertion and maintaining 95-96% oxygen at 8 l/m after the procedure. The patient was admitted, and HRCT revealed giant emphysematous bulla in posteromedial aspects of left lobe. This is to highlight the complications that were observed in post COVID patient.